Arvi In Children Born With Congenital Heart Defects - Ulugbekov Mirzo Ulugbek Oybek Ugli (Genius Journals, 2024)
In the pre-epidemic period of ARI, 31 children aged 3–12 years with congenital heart defects (the main group) were assessed for the effectiveness of a preventive program with recombinant liposomal interferon alpha-2: 250,000 units once a day, 2 times a week for 1 month ( technique I). Due to insufficient effectiveness, we subsequently continued prophylaxis using method II: 250,000 units 2 times a day for 3 days, then 250,000 units once a day, 2 times a week for 1 month.
Keywords: children; method; congenital heart defects